The Concept of Growth Hormone Deficiency Affecting Clinical Prognosis in IVF - Yovich, John L.; Regan, Sheena L. P.; Zaidi, Syeda; Keane, Kevin N. (Frontiers in Endocrinology, 2019)
The current understanding of human growth hormone (hGH; here GH) action is that the molecule is a 191-amino acid, single-chain polypeptide that is synthesized, stored and secreted by the somatotroph cells within the lateral wings of the anterior pituitary gland. It can be classified as a protein (comprising more than 50 amino acids) but true proteins have tertiary and quaternary chains creating a more complex structure, hence hGH is usually classified as a polypeptide. GH is normally secreted at night during sleep and promotes skeletal, visceral and general body growth through the action of somatomedins or IGFs, notably IGF-1. In some tissues, GH action is directed via specific receptors GHRs; these are most abundant in liver, adipose and muscle tissues but have also been shown in granulosa cells, testicular tissues and on the oocyte, as well as in glandular cells of the luteal phase endometrium and decidua; such findings being recent and minimally researched to now. Following engagement with its receptor, the transduction process activates multiple signalling proteins. These all lead to extensive metabolic and mitogenic (growth promoting) responses. Clinically, GH is known to have an important role in pubertal development and is a key hormone for the vigour associated with adolescence and early adult life stages but has a faded presence and role for later adulthood, beyond age 30 years, and is minimally detected in advanced age, beyond 40 years. In association with the rapidly increasing trend for delaying reproduction beyond age 35 years, GH is being widely researched now as a potential adjuvant for infertility treatment in this group who, studies consistently show, have a poorer prognosis than younger females when relying on autologous oocytes. The idea that the age-related reduction in fertility prognosis is a feature of growth hormone deficiency is supported by our studies showing an elevated binding protein IGFBP-3/ IGF-1 ratio and this can be reduced to a normal range (matching younger, good prognosis women) by the administration of GH as an adjuvant.